2022
DOI: 10.3389/fphar.2022.853496
|View full text |Cite
|
Sign up to set email alerts
|

Inspiration for COVID-19 Treatment: Network Analysis and Experimental Validation of Baicalin for Cytokine Storm

Abstract: Background: Cytokine storm (CS) is a systemic inflammatory syndrome and a major cause of multi-organ failure and even death in COVID-19 patients. With the increasing number of COVID-19 patients, there is an urgent need to develop effective therapeutic strategies for CS. Baicalin is an anti-inflammatory and antiviral traditional Chinese medicine. In the present study, we aimed to evaluate the therapeutic mechanism of baicalin against CS through network analysis and experimental validation, and to detect key tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 83 publications
2
14
0
Order By: Relevance
“…The clinical evidence supports the role of some molecules revealed in this work in COVID-19 pathogenesis: ANGPT2 [48,49], CCL2 [50], ICAM1 [52,53], VCAM-1 [52], MIR21 [54], MMP9 [55,56], STAT3 [57], HMGB1 [58,59], SIRT1 [62,63], AGTR1 [66], APOE4 [69,70], ACE [73], CCL11 [86,87], FGF2 [89], TNF [92], PPAR-γ [95], CASP8 [115], IL8 [117], IL6 [118], PRL [119], SP1 [122], TLR4 [123], BDNF [124], CASP1 [125], CASP3 [126,127], IL18 [128], IL10 [129], TGFB1 [130], ANXA2 [131,132], HPSE [162], MAPK1 [163], CDH1 [166], FBN1 [180], GDF15 [182,183], PLAT [195][196][197], RHOA…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The clinical evidence supports the role of some molecules revealed in this work in COVID-19 pathogenesis: ANGPT2 [48,49], CCL2 [50], ICAM1 [52,53], VCAM-1 [52], MIR21 [54], MMP9 [55,56], STAT3 [57], HMGB1 [58,59], SIRT1 [62,63], AGTR1 [66], APOE4 [69,70], ACE [73], CCL11 [86,87], FGF2 [89], TNF [92], PPAR-γ [95], CASP8 [115], IL8 [117], IL6 [118], PRL [119], SP1 [122], TLR4 [123], BDNF [124], CASP1 [125], CASP3 [126,127], IL18 [128], IL10 [129], TGFB1 [130], ANXA2 [131,132], HPSE [162], MAPK1 [163], CDH1 [166], FBN1 [180], GDF15 [182,183], PLAT [195][196][197], RHOA…”
Section: Discussionsupporting
confidence: 80%
“…Intradermal administration of eotaxin-1 upregulated DPP4 in rats [88], constituting a regulatory loop. The elevation of the serum level of fibroblast growth factor 2 (FGF2) in COVID-19 patients was closely associated with disease severity and admission to an intensive care unit [89]. The clinical significance of MMP-9 and HMGB1 in COVID-19 was mentioned above [55,56,59].…”
Section: Dpp4-related Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that studies of the core components and targets showed anti-inflammatory activity in inflammation and immune regulation. Baicalin can be widely used in inflammatory responses caused by viral infections, such as inhibition of pro-inflammatory cytokines (TNF-α, IL-6) in influenza A ( 30 ), inhibition of SARS-CoV-2 RNA-dependent RNA polymerase (RdRp), and angiotensin-converting enzyme 2 (ACE2) activity to prevent SARS-CoV-2 from entering the host cells ( 31 , 32 ). Stigmasterol exerts potential anti-inflammatory effects by inhibiting the IL-1beta-induced NF-kappaB pathway, suppressing pro-inflammatory cytokine expression, and prostaglandin E2 [PGE(2)] production ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, monoclonal antibodies against a variety of cytokines and a variety of related signaling pathway modulatory agents have shown potential to control the SARS-CoV-2 cytokine storm, such as tocilizumab for IL-6 ( 140 , 141 ), emapalumab for IFN-γ ( 142 ), canakinumab for IL-1β and anakinra for IL-1R ( 143 ), JAK2/STAT3 inhibitors ( 131 , 144 ), NF-κB pathway regulators ( 145 ), MAPK/NF-κB pathway regulators ( 146 ), the nucleotide-binding and oligomerization domain-like receptor family pyrin domain-containing 3 inflammasome signaling inhibitors ( 147 , 148 ). In addition, immunoglobulin ( 149 ), nanotechnology-based corticosteroid drugs ( 150 ), and traditional Chinese medicine ( 151 153 ) are also potential drugs to alleviate cytokine storms.…”
Section: Discussionmentioning
confidence: 99%